Challenges Encountered by Different Banquet and Catering Services during Pandemic Located at Brgy. Commonwealth, Quezon City: Towards a Guide: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Catering services have been a fast-growing industry for years, but the pandemic in 2020 became the worst. During the COVID-19 pandemic, the banquet and catering businesses were shut down, causing profit and employment loss. It affected many people, communities, and businesses worldwide, and the catering industry felt the severe effects of this pandemic. There were challenges that this industry faced throughout the pandemic phase, which led to companies being temporarily closed due to lockdowns and restrictions. Adjusting to this new normal was more challenging than people thought. Before conducting an event, they had to check the capacity of the venue due to different health protocols to follow. The number of guests was limited, and some events were cancelled due to lockdowns in certain places. With this existing condition, the researchers conducted a study that determined the challenges encountered in banquet and catering services during the pandemic that affected employees and employers. The research used the descriptive technique to identify the challenges in banquet and catering services during the pandemic and draw lessons from experience. The researchers gathered data using survey questionnaires administered via Google Forms to a mixed number of fifty (50) employers and employees from the banquet and catering services in Brgy. Commonwealth, Quezon City, as our target respondents. The online survey results revealed that most respondents were between the ages of 18-22 years old, mostly female and single. Most of their work positions were service personnel, and 66% of the population preferred to have their preparations two days before the event. During the pandemic, the respondents admitted that they were greatly affected by salary, schedule, location, transportation, and health. Respondents faced many challenges that burdened them while working in the industry, particularly having social distancing while at an event. Every business had to adjust, which may be more difficult for some than others, with a percentage of 90. Based on the gathered data and conclusions drawn, the researchers evaluated and determined the challenges different banquet and catering services encountered during the pandemic. This study focused on gathering ways to overcome the banquet and catering services' challenges to help the industry grow. The gathered data will provide critical factors in the commitment to the economic success of the catering industry amidst the pandemic. To overcome the challenges, the faculty should utilize modern ways of teaching in this new normal and assist the students in basic learning in their chosen field of expertise in the hospitality industry. This could give motivation to the students, the desire to graduate, awareness of current opportunities, and the drive to pursue their chosen career. Respondents also recommended that the faculty communicate efficiently and effectively with online learners to prepare them for their careers amidst the new normal. The administration should employ more knowledgeable career and skills-related webinars in well-known, accredited institutions locally and abroad to inspire and expose the students to their career opportunities.